Digital Educational Data Management Resolving System Synchronization Inconsistencies: Manajemen Data Pendidikan Digital Mengatasi Inkonsistensi Sinkronisasi Sistem - Fira Arma Atus Solicha; Isnaini Rodiyah; Dinda Rahmawati Mujiarto P; Sekar Ayu Purwanti; Dila Dwi Andayani; Ari Yohanes Decaprio (International Consortium of Education and Culture Research Studies, 2025)
General Background Digital transformation necessitates accurate information management across the educational sector. Specific Background The Basic Education Data mechanism serves as Indonesia's primary instrument for national academic information collection. Knowledge Gap Despite its crucial role, substantial discrepancies remain between policy expectations and technical realities, particularly regarding operator capacity and infrastructure readiness. Aims This study analyzes the digital administration workflow at a senior high school to identify prevailing operational obstacles. Results The findings reveal that while organizing stages function adequately, critical technical barriers emerge from demographic spelling mismatches and server latency, resulting in severe integration delays. Furthermore, frequent application updates severely burden human resources. Novelty This study specifically isolates civil registry integration mismatches as the primary bottleneck in school-level administrative digitalization. Implications Addressing these infrastructural limitations will streamline national academic accuracy, requiring targeted operator training and stabilized application policies. Highlights: Civil registry identity mismatches frequently create invalid records and delay national integration. Frequent policy changes and application updates overwhelm school operators lacking specialized technical training. Targeted human resource capacity building stabilizes administrative workflows during technological transitions. Keywords: Educational Administration, Information Technology, School Operators, Digital Transformation, Academic Records